Introduction: Transnational cinema at the borders: borderscapes and the cinematic imaginary - Mendes, Ana Cristina (2018)
In tandem with a postnational imaginary that is nurtured by the ever-present promise of deterritorialized mobility and burgeoning migratory fluxes, walls and fences separating nation-states multiply. This is a burning issue: Even though nation-states at the centre of the global order increasingly present themselves as postnational, calls for tighter border security undermine utopian notions of both a borderless New Europe and the US as the Promised Land. This collection investigates the urgent issue of borderscapes and the cinematic imaginary by bringing together a range of new approaches in the field of film and media studies, crossing over into sociology, migration studies and artistic research. The contributions focus on the interrelated motifs of borderscapes as they are represented and used in transnational cinematographies, from Palestine to Sweden, Spain, Finland, Italy, Iran, Iraq, France, the UK and the US, and as constituting premises of cinematic production. The chapters in this book were originally published in the Transnational Cinemas journal.